Transcatheter Aortic Valve Replacement With a Repositionable Self-Expanding Prosthesis - Søndergaard, Lars; Rodés-Cabau, Josep; Hans-Peter Linke, Axel; Fichtlscherer, Stephan; Schäfer, Ulrich; Kuck, Karl-Heinz; Kempfert, Joerg; Arzamendi, Dabit; Bedogni, Francesco; Asch, Federico M.; Worthley, Stephen; Maisano, Francesco (Journal of the American College of Cardiology, 2018)
The new self-expanding, repositionable transcatheter heart valve (THV) system was designed for treatment of severe, symptomatic aortic stenosis in patients with high surgical risk. The purpose of this study was to report 1-year outcomes of transcatheter aortic valve replacement with the new THV system. This ongoing, international, multicenter study evaluated patients with severe, symptomatic aortic stenosis implanted with the THV via transfemoral access and follow-up at 30 days, 1 year, and annually through 5 years. The primary endpoint is all-cause mortality at 1 year; secondary endpoints include clinical outcomes and echocardiographic measurements, both adjudicated. A total of 941 patients (82.4 ± 5.9 years; 65.7% female; Society of Thoracic Surgeons Predicted Risk of Operative Mortality score: 5.8%) were enrolled and underwent an implant at 61 sites in Europe, Australia, and Canada. At 1 year, Kaplan-Meier estimates for all-cause mortality, cardiovascular mortality, disabling stroke rates, and myocardial infarction were 12.1%, 6.6%, 2.2%, and 2.5%, respectively. Mean aortic transvalvular gradient and aortic valve area were 8.66 mm Hg and 1.75 cm2, respectively. Paravalvular leakage was moderate or higher in 2.6% of patients with no severe leakage. New pacemaker rates were 18.7% and 21.3% for pacemaker naïve patients at 30 days and 1 year, respectively. Functional class, exercise capacity, and quality of life improved significantly from baseline to 1 year. Transcatheter aortic valve replacement with the new THV in patients who are at increased surgical risk is associated with low 1-year mortality and stroke rates. Favorable hemodynamic results at 1 year are observed with low transvalvular pressure gradient and incidence of significant paravalvular leakage. (5 Year Observation of Patients With PORTICO Valves [PORTICO-I]; NCT01802788) [Display omitted]